2015
DOI: 10.1038/ncomms6845
|View full text |Cite
|
Sign up to set email alerts
|

An acetylation switch controls TDP-43 function and aggregation propensity

Abstract: TDP-43 pathology is a disease hallmark that characterizes amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD-TDP). Although a critical role for TDP-43 as an RNA-binding protein has emerged, the regulation of TDP-43 function is poorly understood. Here we identify lysine acetylation as a novel post-translational modification controlling TDP-43 function and aggregation. We provide evidence that TDP-43 acetylation impairs RNA-binding and promotes accumulation of insoluble, hyper-phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
340
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(347 citation statements)
references
References 68 publications
3
340
4
Order By: Relevance
“…In this work, we have demonstrated that the formation of large aggregates does not depend on oxidation of cysteine residues, but rather on partial unfolding of the hydrophobic core of the protein, with subsequent deformation of the β-strands. This is suggested by our in silico data and by previous indication that partial unfolding of TDP-43 may descend both from oxidation, acetylation and from loss of TDP-43 binding to its natural interactors (Cohen et al, 2015).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…In this work, we have demonstrated that the formation of large aggregates does not depend on oxidation of cysteine residues, but rather on partial unfolding of the hydrophobic core of the protein, with subsequent deformation of the β-strands. This is suggested by our in silico data and by previous indication that partial unfolding of TDP-43 may descend both from oxidation, acetylation and from loss of TDP-43 binding to its natural interactors (Cohen et al, 2015).…”
Section: Discussionmentioning
confidence: 57%
“…Oxidative stress promotes TDP-43 cysteine oxidation and disulfide crosslinking; it also promotes TDP-43 acetylation on K145 and K192, possibly because aggregation prevents effective HDAC6 binding under exposure to potent oxidative stimuli (Cohen et al, 2012(Cohen et al, , 2015. Aggregated TDP-43 is also hyper-phosphorylated on C-terminal serine residues, although several studies suggest that phosphorylation prevents rather than promotes TDP-43 aggregation (Li et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…More recently, formation of TDP-43 truncated form was shown to be generated by abnormal splicing using an alternate translation initiation codon (ATGMet85) with this isoform being associated with pathological inclusion bodies [39]. TDP-43 acetylation switch was also demonstrated to participate in its toxicity and aggregation [40]. Finally, TDP-43 was shown to play an important role in the formation and the axonal transport of mRNA/stress granules, with ALS-causing TDP-43 mutations being capable of selectively abrogating this process [41 && ].…”
Section: Aggregation Initiation Of Amyotrophic Lateral Sclerosis-assomentioning
confidence: 98%
“…K-Q) exhibit a 50 %-65 % decrease in mRNA binding efficiency and readily form cytoplasmic aggregates. Similar wild-type TDP-43 aggregates can also be induced by oxidative stress but co-expression of a histone deacetylase (HDAC6) deacetylates cytoplasmic TDP-43 under basal conditions but not in stress-induced aggregates [51,54]. Thus TDP-43 acetylation regulates its RNA-binding and subcellular localization, although it is unclear whether these two processes are distinct or linked and TDP-43 acK may be dysregulated by environmental stress.…”
Section: Transactive Response Dna-binding Protein -43mentioning
confidence: 99%